Analysis of feeding pattern and health practices in child 6-24 months nutritional status in Makassar, Bugis and Toraja tribes - Armenia Eka Putriana; Drajat Martianto; Hadi Riyadi (AcTion: Aceh Nutrition Journal, 2019)
The cultural practices of eating in the Makassar, Bugis and Toraja tribes have a variety of unique characteristics based on their respective beliefs. Objective of this study was to analyze the practice of feeding pattern and health practices in child under two years nutritional status in Makassar, Bugis and Toraja tribes. The study using a cross-sectional study design. Total 360 child under two years were divided into 3 tribes: 120 in Makassar tribes, 120 in Bugis tribes and 120 in Toraja tribes. The results showed that there were significant differences in parenting feeding pattern on cultural. The parenting feeding pattern style applied by child under two years mothers is mostly in the Toraja tribe (OR: 1,6), less than the Makassar and Bugis tribes. Health parenting in Bugis tribe (OR: 8,1) is better than the Toraja and Makassar tribes. In conclusion, the highest percentage of parenting feeding pattern styles in the less category is Makassar tribe and the highest percentage of health care patterns in the good category is Toraja tribe. Praktek terhadap budaya makan di suku Makassar, Bugis dan suku Toraja memiliki berbagai karakteristik unik berdasarkan keyakinan masing-masing. Tujuan penelitian untuk menganalisis praktik pola makan dan praktik kesehatan serta analisis status gizi pada anak di bawah dua tahun pada suku Makassar, Bugis dan suku Toraja. Penelitian menggunakan desain potong lintang. Total sampel yaitu 360 anak di bawah dua tahun yang berasal dari 3 suku: 120 di suku Makassar, 120 di suku Bugis dan 120 di suku Toraja. Hasil penelitian menunjukkan terdapat perbedaan signifikan terhadap pola makan orang tua pada budaya. Model pola asuh makan yang diterapkan kepada anak dibawah dua tahun oleh ibu sebagian besar berada di suku Toraja kurang baik (OR: 1,6), dibandingkan dari suku Makassar dan Bugis. Pelayanan kesehatan oleh orang tua kepada anak-anak mereka di suku Bugis (OR: 8,1) lebih baik dari pada suku Toraja dan Makassar. Kesimpulan, persentase tertinggi pola pola asuh makan dalam kategori kurang adalah suku Makassar dan persentase tertinggi pola perawatan kesehatan dalam kategori baik adalah suku Toraja.